2015
DOI: 10.1128/jvi.01884-15
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus saimiri MicroRNAs Preferentially Target Host Cell Cycle Regulators

Abstract: In latently infected marmoset T cells, H erpesvirus saimiri (HVS) is a T-lymphotropic gammaherpesvirus that causes acute T-cell lymphomas and leukemias inNew World primates and transforms human primary T cells in vitro (1). The most abundant transcripts in HVS latently infected marmoset T cells are seven noncoding U-rich RNAs, known as HSURs (H. saimiri U-rich RNAs) (2). The functions of these viral noncoding RNAs are not well understood. HSUR1 forms base-pairing interactions with a host microRNA (miRNA), miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…As a result, in the beginning of our classification we could divide them into host miRNAs and viral miRNAs, according to their source (Table 1). Similar to host miRNAs, the viral ones participate in the life cycle of the virus and could induce certain modifications in the host cells (Guo et al, 2015;Bruscella et al, 2017). Likewise, they are also processed by the previously mentioned RNases Drosha and Dicer, although some viral miRNAs have been described to skip the first step and pass directly to Dicer processing (Bogerd et al, 2010;Diebel et al, 2010;Tycowski et al, 2015).…”
Section: Classification Of Micrornas Involved In Viral Infectionsmentioning
confidence: 99%
“…As a result, in the beginning of our classification we could divide them into host miRNAs and viral miRNAs, according to their source (Table 1). Similar to host miRNAs, the viral ones participate in the life cycle of the virus and could induce certain modifications in the host cells (Guo et al, 2015;Bruscella et al, 2017). Likewise, they are also processed by the previously mentioned RNases Drosha and Dicer, although some viral miRNAs have been described to skip the first step and pass directly to Dicer processing (Bogerd et al, 2010;Diebel et al, 2010;Tycowski et al, 2015).…”
Section: Classification Of Micrornas Involved In Viral Infectionsmentioning
confidence: 99%
“…Similarly, miR-US25-1-5p encoded by hCMV was shown to target multiple cellular genes to inhibit viral replication (63). Further supporting the role of Multiple components of the host secretory pathway Immune evasion (reduced cytokine secretion) (100) herpesvirus miRNAs in restraining reactivation, a recent report has shown that miR-HSUR4-3p present in the herpesvirus saimiri (HVS) U-rich RNAs (HSURs) could repress the expression of the p300 transcriptional coactivator by binding the open reading frame of its mRNA (64).…”
Section: Herpesvirus-encoded Mirnas Target Viral and Cellular Transcrmentioning
confidence: 96%
“…Interestingly, HVS miR-HSUR5-3p downregulated WEE1, a negative regulator of cell cycle progression, leading to reduced phosphorylation of its substrate, cyclin-dependent kinase (CDK1) (64). Furthermore, several studies have shown the potential role of some EBV and hCMV miRNAs in inhibiting cell apoptosis through restriction of expression of pro-apoptotic proteins (66)(67)(68)(69).…”
Section: Survival and Proliferation Of Latently Infected Cells And Hementioning
confidence: 98%
See 1 more Smart Citation
“…In addition, a 3.91 kb lncRNA M3‐04 generated by gammaherpesviruses regulates viral replication in mice by interacting with antisense miRNAs and the latency gene M2 . Other herpesviruses also encode multiple functional lncRNAs, such as the Epstein‐Barr virus encoding ncRNA, BamH I‐A rightward transcripts, Kaposi's sarcoma‐associated herpesvirus (KSHV) encoding UCA1 , and herpesvirus saimiri encoding U‐rich RNAs . Additionally, the 3′‐untranslated region (UTR) of the flavivirus RNA genome is capable of transcribing an active lncRNA, termed the subgenomic flavivirus RNA (sfRNA), which protects viral RNAs from degradation by the host nuclease Xrn1 and suppresses antiviral RNA interference (RNAi) in infected human cells in culture and, also, interestingly, in mosquitoes by direct interaction with the RNAi machinery .…”
Section: Differential Expression Of Lncrnasmentioning
confidence: 99%